THE INDIA-US-CHINA TRIANGLE: CRAFTING THE BLUEPRINT FOR A NEW WORLD ORDER - Mir, Musssaib Rasool; Kumar, Santosh; Bhat, Shabir Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The strategic triangle established by China, the US, and India has sparked a renewed discussion in modern international relations study on the implications of their interactions for the formation of a new world order. The fundamental characteristics of the trilateral relationship of India, US and China inevitably lead to a mixture of conflict and collaboration, as well as feelings of anxiety, uncertainty, and reluctance. The border dispute between China and India, coupled with their recent economic and technological advancements, has concerned strategists and experts in foreign policy about the potential for the conflict to escalate and the threat it poses to the US so called peaceful post-cold war global order. The conversation about the narratives of the emerging world order has been reignited by the visit of US National Security Advisor Jake Sullivan to India on June 13, 2023; Secretary of State Antony Blinken's visit to China on June 18, 2023; and Prime Minister Modi's State visit to the USA on June 21–24, 2023. Therefore, the study is an attempt to comprehend the emergence of a new international order with the relative ascendance of China and India, the rise in the narratives about the declining influence of the United States, and the antagonistic relationship between China and India on the one hand coupled with confrontational attitude of China-US on the other hand.